Menakar Struktur Kepemilikan Saham dan Kinerja Perusahaan - Mayroza Wiska (Jurnal Manajemen dan Bisnis, 2020)
ABSTRACTAnalysis of Performance Shareholding Structure of the Company (a mining company listed on the Indonesia Stock Exchange. In preparation of this paper, the authors have conducted research on the Indonesia Stock Exchange (Capital Market Information Center-Padang) Jl.Pondok 90 Padang. The purpose of this study was to determine the effect of ownership structure on corporate performance in the mining company listed on the Indonesia Stock Exchange (BEI. The analysis in this research using descriptive statistics, classic assumption test (test mulitikolonieritas, autokolerasi test, normality test), analysis of regression coefficient test, partial regression coefficients (t test), testing regression coefficients together (test f). As for the overall analysis of this data with the help of a software program SPSS version 21.0 for Windows. Results of this study concluded that: (1) public ownership structure positively affects the performance of companies in the mining company listed on the Indonesia Stock Exchange (BEI). (2) The structure of stock ownership is not a positive influence on the company's performance in the mining company listed on the Indonesia Stock Exchange (BEI). (3) The structure of public ownership and foreign ownership together affect the company's performance in the mining company listed on the Indonesia Stock Exchange (BEI).